Cliche as a Structural Element of Scientific Text - Bareikytė, Zina (Kalbotyra, 2004)
The aim of the given article is to disclose the role played by stable word-combinations-cliches in the structure of a coherent global English scientific text and establish whether they form part and parcel of any scientific discourse.It has been found that stable word-combinations-cliches are present at all levels of scientific discourse and contribute to the formation of a global scientific text. They are introduced into the text as readymade and fully reproducible linguistic units without which one could find it difficult, if not impossible, to produce a text which may be called “scientific” in the proper sense of the word.